The Emergence of Social Class in Gundala Film (Indonesia) and The Hunger Games (America) - Rahma Hayati Harahap; Fatia Syarifah Nasution (Linguistik, Terjemahan, Sastra (LINGTERSA), 2024)
Movies also tell a variety of problems, one of which is the existence of social class. Social class is the division of classes in society based on certain criteria, be it religion, economy, education, status and others. Gundala is a 2019 Indonesian hero movie directed by Joko Anwar. In the movie, Sancaka (Abimana Aryasatya) is the main character. The Hunger Games is a 2012 American science fiction film directed by Gary Ross, based on the novel of the same name by Suzanne Collins. This research aims to discuss the existence of a picture of the prominence of social class in the film Gundala and also the film The Hunger Games. In this study, several explanations about social class are taken. The method used in this research is descriptive qualitative method, using unit of analysis in the form of texts. This research also uses the theory of social class according to Karl Max, and the results of this study show that the division of social classes is real, creates class struggle, and becomes one of the points of conflict in society.